Non-severe eosinophilic granulomatosis with polyangiitis: long-term outcomes after remission-induction trial. (5th May 2019) - Puéchal, Xavier; Pagnoux, Christian; Baron, Gabriel; Lifermann, François; Geffray, Loïk; Quémeneur, Thomas; Saraux, Jean-Luc; Wislez, Marie; Cottin, Vincent; Ruivard, Marc; Limal, Nicolas; Aouba, Achille; et al.
Abstract: Objective: In a previous controlled trial, 1-year adjunction of AZA to glucocorticoids (GC) for patients with non-severe, newly diagnosed eosinophilic granulomatosis with polyangiitis (EGPA) failed to lower remission failure, vasculitis relapse and isolated asthma/rhinosinus exacerbation rates, or cumulative GC use at month (M) 24. The aim of this study was to analyse longer-term outcomes to determine whether subsequent vasculitis relapse or isolated asthma/rhinosinus exacerbation (IARE) rates differed. Methods: After M24, patients were followed prospectively, being treated based on physicians' best judgment. Flares and reasons for increased GC dose or immunosuppressant use were recorded, and reviewed according to randomization group to distinguish vasculitis relapses from IAREs according to EGPA Task Force recommendations. Results: Fifty EGPA trial participants were followed for a median (interquartile range) of 6.3 (5.4–7.6) years; two (4%) died 11 months post-inclusion. By M24, vasculitis had relapsed in 21/49 (43%) patients and 14/50 (28%) had IAREs. Another patient died 4.8 years post-inclusion (infection). Among nine patients with subsequent vasculitis relapses, three had a major relapse and three had their first relapse after M24; among 25 patients with later IAREs, 17 occurred after M24. At 5 years, respective vasculitis relapse and IARE rates were 48% (95% CI 34.0, 62.6) and 56% (95% CI 41.7, 70.8), with no between-arm differences ( P = 0.32 and 0.13). No entry clinical or biological parameter was associated with these outcomes during follow-up. Conclusion: These results confirmed that 1-year AZA and GC induction obtained good overall survival but no long-term benefit for non-severe EGPA patients. Vasculitis relapses, occurring mostly during the first 2 years, and IAREs, occurring throughout follow-up, require other preventive treatments. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT00647166.